INTELLIGENT INFORMATION TECHNOLOGY FOR OBTAINING TRUST DECISIONS BASED ON THE ONTOLOGY OF TRUST IN A HUMAN-CENTERED APPROACH (Computer systems and information technologies, 2022)
The paper presents the results of research on the development of intelligent information technology for obtaining trust decisions to determine the constituent elements and the interaction between them, which together provide for obtaining trust decisions. Ethical principles based on human-centered approach have been identified, which formed the basis for the development of a set of methods for the practical implementation of certain principles.The set of developed methods to ensure certain ethical principles of trust in decisions obtained using intelligent information systems has allowed developing intelligent information technology for obtaining trust decisions. Confidence in decisions is formed by ensuring the practical implementation of ethical principles in the methods of processing input information. Information technology determines the interaction of the developed methods, which together form the trust in the decisions of the information system. The structure of formation of intelligent information technologies for obtaining trust decisions is presented, as well as the structure of interaction of components of intelligent information technologies for obtaining trust decisions. A description of ethical principles with the definition of their implementation in the structure of a set of methods is given. The set of functions which realization allows reaching application of the offered intellectual information technology is defined.The components of the concept of trust were considered within the concept of intelligent information technology. The practical application of intelligent information technology is generally seen as a complex system of interconnected structural components to solve practical problems with building ecosystems for intelligent information technology, ensuring trust at all stages of the life cycle of intelligent information technology with a chain of trust and continuity.
Keywords: intelligent information technology; ethical principles of trust; difficult to classify information